Penggunaan Teknik Ice Breaking Untuk Meningkatkan Jiwa Kewirausahaan Siswa Di Sekolah Menengah Kejuruan (SMK) - sanjaya, alga (Universitas Negeri Makassar, 2017)
This study examines Ice Breaking Techniques Through Career Guidance to Improve Student Entrepreneurship Soul in Vocational Secondary School (SMK). The main problems of this research are: 1. How is the description of student entrepreneurship spirit in SMK? 2. How to use ice breaking technique as an effective solution to improve student entrepreneurship spirit in SMK? The purpose of this study are: 1. To know the description of the level of student entrepreneurship spirit in SMK. 2. To know ice breaking technique as an effective solution to improve student entrepreneurship spirit in SMK. This research uses library research method by collecting data from various relevant sources, then researcher explain problem solving through synthesis and draw conclusion. The results showed that: 1. The level of entrepreneurship of students in SMK is still low. 2. The use of ice breaking technique through career guidance as an effective solution offered by researchers to improve students entrepreneurship spirit in SMK.